Threats to Heritage in Cultural Keystone Places: Fitting Western Concepts into Gitxsan Legal Orders and Laws - Ardythe Wilson Dimdiigibuu; Chelsey Geralda Armstrong (Ethnobiology Letters, 2025)
Resource extraction poses significant threats to cultural heritage sites and landscapes across British Columbia (BC, Canada), particularly in Gitxsan Territories, where people’s values are often overlooked in archaeological heritage management and consulting contexts. This research explores how Gitxsan legal orders and stewardship principles can contribute to conserving and restoring culturally and ecologically significant places—crucial work in the face of ongoing colonial policies and an increasingly changing climate. Cultural landscapes, characterized by the Lax’yip (Gitxsan Wilp/House Territories), provide a foundation for understanding long-standing stewardship practices and relationships that underscore cultural and environmental values and well-being. A key challenge, however, is how to effectively represent these landscapes to outsiders who may not share the same cultural connections to the land or understand Gitxsan heritage, histories, laws, and protocols. Reviewing these tensions in the context of resource extraction in one Territory, Lax Xsin Djihl, Wilp/House histories and stewardship practices are routinely ignored by archaeological consultants, leading to the destruction of cultural heritage. Evocative metaphors, such as cultural keystone places, may offer a way to convey the ecological and cultural realities of Territories for Gitxsan Houses, fostering a broader understanding and deeper regard for Gitxsan cultural heritage within archaeological regulatory frameworks.